FRI0295 DLCO /VA: A Possible Predictor of Pulmonary Vascular Disease in Systemic Sclerosis. (15th July 2016) - Corzo, P.; Pros, A.; Polino, L.; Marques, D.; Balcells, E.
Abstract : Background: Pulmonary function tests (PFTs) are used for screening of pulmonary involvement in systemic sclerosis (SS). Decreased DLCO is the earliest and most sensitive alteration detected. It has been seen that there are some SS patients with reduced values of DLCO (<80%) who have no demonstrable ILD by HRCT or pulmonary arterial hypertension (PAH) criteria by screening methods (pulmonary artery pressure (PAP) and tricuspid regurgitation (TR), by echocardiography). DLCO divided by the alveolar volume (DLCO/VA) is usually normal or moderately low in the ILD; its drop suggests an alveolar-capillary membrane dysfunction, thus might suggest the presence of a possible pulmonary vascular disease (no-PAH) related to SS, like in other locations, or could be a predictor of PAH presence Objectives: To describe and compare the clinical, immunological, echocardiographic and spirometric data of two patients groups with SS and decreased DLCO; differentiating those with unknown causes for the DLCO and DLCO/VA decrease, suggestive of alveolar-capillary membrane disease, from those with ILD, PAH or other pulmonary disease associated which could justify this finding Methods: Retrospective review of a hospital cohort of 115 SS patients. All patients with DLCO <80% were included. We defined: "Cases", patients with DLCO/VA decreased without known causes for DLCO decrease, and "controls", patients with a known cause of decreased DLCO: PAH (PAP>36mmHg by echocardiogram), ILD by HRCT, two groups were compared FVC <80%, FEV <80% or other known lung disease Results: 75 patients with SS and DLCO <80%, 20 cases and 55 controls, were compared. We found statistically significant differences in the pattern disease, with a greater proportion of cases with limited SS (LSS) and anticentromere Ab positive whereas predominance of diffuse SS (DSS) and antiScl70 positive in controls. Esophageal involvement was higher in controls and tricuspid regurgitation (TR) higher in cases (p<0.005). "Cases" had mean values: DLCO: 65.60%, DLCO/VA: 62.65%, PAP: 26.29mmHg, right atrial diameter: 12.10cm 2 and max. tricuspid speed: 2.23m/s. There were no differences in sex, evolution time, the presence of digital ulcers, telangiectasia, Raynaud's phenomenon, ischemic heart disease, smoking, or in the capillaroscopic pattern. Conclusions: There are a group of patients with SS, LSS and anticentromere Ab positive predominantly, without respiratory symptoms and decreased DLCO/VA with no justifiable cause. The decrease in DLCO/VA suggest the existence of an alveolar-capillary membrane dysfunction.These patients often present TR without PAH by echocardiographic criteria, so there might be some alteration of the lungs microvasculature suggesting a "pre-PAH" pattern.We should consider a subgroup of patients who would be candidates, in clinical practice, to the application of the DETECT algorithm, cardiorespiratory response to exercise testing and/or cardiac hemodynamic study, despite the absence of symptoms and PAH criteria by ultrasound Disclosure of Interest: None declared